The association between the amount of fetal fraction in cell-free DNA testing and adverse pregnancy outcomes: A cohort study - Maryam Aryavand; Maryam Nurzadeh; Marjan Ghaemi; Sina Eskandari Delfan; Vajiheh Marsoosi (International Journal of Reproductive BioMedicine)
Background: Noninvasive perinatal testing is a new method of screening for aneuploidy called cell-free DNA (cfDNA). Fetal fraction (FF) plays a crucial role in assessing the reliability of aneuploidy detection through noninvasive perinatal testing.